2019
DOI: 10.1111/tbed.13346
|View full text |Cite
|
Sign up to set email alerts
|

Identifying emerging trends in antimicrobial resistance using Salmonella surveillance data in poultry in Spain

Abstract: Despite of controls and preventive measures implemented along the food chain, infection with non‐typhoidal Salmonella (NTS) remains one of the major causes of foodborne disease worldwide. Poultry is considered one of the major sources of NTS. This has led to the implementation of monitoring and control programmes in many countries (including Spain) to ensure that in poultry flocks infection is kept to a minimum and to allow the identification and monitoring of circulating NTS strains and their antimicrobial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…As presumed, the level of resistance to the antimicrobials used in our study was closely linked with the Campylobacter bacterial species found, with higher levels of resistance in C. coli than in C. jejuni in agreement with previous research (Pergola et al, 2017;Alvarez et al, 2020). The lack of barriers to horizontal gene transfer (HGT) in C. coli may explain the higher levels of MDR observed in this bacterial species compared to C. jejuni (Pearson et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As presumed, the level of resistance to the antimicrobials used in our study was closely linked with the Campylobacter bacterial species found, with higher levels of resistance in C. coli than in C. jejuni in agreement with previous research (Pergola et al, 2017;Alvarez et al, 2020). The lack of barriers to horizontal gene transfer (HGT) in C. coli may explain the higher levels of MDR observed in this bacterial species compared to C. jejuni (Pearson et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, it is of paramount importance to explore the genetic mechanisms implicated in AMR in C. coli and C. jejuni from the different hosts involved in the epidemiology of infection in humans (EFSA-ECDC, 2020). As described elsewhere, this study of isolate-based phenotypic data versus aggregated data has also proven to be a reliable means of gaining insight into such mechanisms (Alvarez et al, 2020), and the assessment of phenotypic susceptibility patterns found here can guide the genetic analysis in a "top-down" approach (Sheppard and Maiden, 2015). The annual proportion of Campylobacter positive samples found in our samples from broilers collected over a 17-year period (ranging from 26.2 to 76.7%) was higher than values reported by EFSA from EU member states (26%) (EFSA-ECDC, 2019a) and mostly higher than values reported in other regions of the world such as China (30.2%) (Tang et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies on colistin susceptibility of Salmonella spp. utilizing surveillance data from poultry, food and human clinical sources in European countries and the United States, have indicated a correlation between Salmonella serotype and colistin MICs (Tyson et al, 2018;Alvarez et al, 2019). Though the occurrence of Salmonella serotypes vary from different countries and sources, the inhomogeneity was confirmed in the current study in which the high rate of colistin resistance of Salmonella spp.…”
Section: Discussionsupporting
confidence: 70%
“…However, the usefulness of serotype-based identification for epidemiological purposes is limited because it may lead to the clustering of highly unrelated strains [62]. For this reason, we performed the present study based on whole genome sequencing (WGS) analysis in an attempt to assess the genetic relatedness between S. Kentucky strains circulating in poultry species in Spain, given the recent reports of the presence of MDR isolates belonging to this serotype [24].…”
Section: Discussionmentioning
confidence: 99%
“…Kentucky isolates were included in the study (Table S3) so that all hosts (laying hen, broiler or turkey), years (2011–2017) and AMR profiles (AGSuT/non-AGSuT) were represented (Table S3). Eleven (16.7 %), 27 (40.9 %) and 28 (42.4 %) isolates were retrieved from laying hen, broiler and turkey, respectively, roughly representing the proportions of isolates from each host among the 228 isolates [24]. The farms of origin of 56 isolates (no information was available for ten isolates) were in 21 provinces of Spain, with most laying hen and turkey farms being in the South and East of the country while broiler farms were more scattered (), in agreement with the overall distribution of the poultry farms from each production type in Spain based on farms sampled in the frame of the national Salmonella control programme ().…”
Section: Methodsmentioning
confidence: 99%